HELICITY WAVE-FUNCTIONS FOR MASSLESS AND MASSIVE SPIN-2 PARTICLES - Spehler, D.; Novaes, Sérgio Ferraz [UNESP] (American Physical Soc, 1991)
Starting from general properties of a spin-2 field, we construct helicity wave functions in the framework of the Weyl-van der Waerden spinor formalism. We discuss here the cases of massless and massive spin-2 particles.